Whispering gallery mode microlasers and refractive index sensing based on single polymer fiber. Issue 1 (24th January 2013) - Duong Ta, Van; Chen, Rui; Ma, Lin; Jun Ying, Yong; Dong Sun, Han
<x xml:space="preserve">Abstract</x> The realization of whispering gallery mode (WGM) lasing in polymer fibers is hindered by an appropriate method to dissolve the polymer and the gain material. In this work, microfibers fabricated by directly drawing from a dye doped polymer solution are exhibited as high quality microlasers and microsensors. Multi‐mode and even single‐mode lasing is observed from the fiber under optical pumping at room temperature. The linewidth of lasing mode is narrower than 0.09 nm. The lasing mechanism is unambiguously verified by comprehensive spectroscopic analysis and ascribed to WGMs. Diameter‐ and polarization‐dependent lasing characteristics are systematically investigated, showing good agreement with the theoretical calculation. Particularly, application of the fiber laser for refractive index sensing based on resonant shift of lasing mode is demonstrated and the sensitivity up to about 300 nm/RIU is achieved. The promising potential of high quality polymer microfibers as optical sensors and multi‐function components for flexible photonic integrated systems is highly expected. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>